The Effect Of Corporate Social Responsibility, Job Crafting, Employee Motivation, Employee Engagement And Job Satisfaction On Organizational Commitment - Nurstefani Dwi Putri; Justine Tanuwijaya; Andreas Wahyu Gunawan Putra (UNIVED Press, 2025)
The present study investigates the intricate relationships among corporate social responsibility (CSR), job crafting, employee motivation, employee engagement, organizational commitment, and job satisfaction within the domain of Indonesian vocational higher education institutions. Employing a quantitative research methodology, data were gathered from a sample of 254 participants through a structured questionnaire administered in 2024. Structural Equation Modeling (SEM) was utilized to examine the hypothesized relationships among the variables. Empirical findings indicate that CSR, employee motivation, and employee engagement exert a significant positive influence on job satisfaction. Furthermore, job satisfaction demonstrates a substantial positive impact on organizational commitment. Notably, the study revealed that while CSR does not directly affect organizational commitment, it indirectly influences this outcome through its positive association with job satisfaction. Both employee motivation and engagement were found to significantly enhance organizational commitment, both directly and indirectly via job satisfaction. These results underscore the critical role of job satisfaction in fostering organizational commitment. Consequently, the study recommends that vocational higher education institutions prioritize the enhancement of CSR initiatives, the cultivation of employee engagement, and the implementation of equitable decision-making processes to cultivate heightened job satisfaction and organizational commitment.